Penerapan Jaringan Syaraf Tiruan Dalam Pengenalan Huruf Aksara Suku Karo dengan Metode Perceptron - Desi Rahma Yani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Recognition of letters is one of the capabilities of artificial neural networks (ANN) both recognition of facial patterns, fingerprints, handwriting and character patterns, and printouts. The problem experienced in the introduction of the Karo tribe is the difference between the letters of the alphabet and the letters of the script very different, both in form and how to read it, and must be able to recognize each one of the letters. In learning the karo tribe, a person can experience difficulty in learning it. Therefore, the introduction of karo characters is needed to avoid mistakes in the introduction of Karo tribe letters and makes it easier for the public to know or recognize the characters of the karo tribe. The perceptron method is able to recognize the karo characters which will result in the recognition that the image object can be recognized by the network, making it easier for humans to manage data in a program through a pattern of input that is recognized in advance so that the network can be made from a black and white image